Pelatihan Senam Kreasi Daerah Biteya di SD Negeri 75 Kota Tengah: Upaya Revitalisasi Budaya Lokal dalam Pembelajaran Penjas - Ella H Tumaloto; Al Ilham; Sulasikin Sahdi Kadir; Haerul Ikhsan (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2025)
The lack of utilization of local wisdom-based gymnastics and the monotonous models used in Physical Education classes served as the background for the implementation of the Biteya traditional creative gymnastics training at SD Negeri 75 Kota Tengah, Gorontalo City. This training aimed to enhance the skills of teachers and students in applying culturally based PE learning. The training was carried out in three stages: preparation, implementation, and evaluation. Participants included three PE teachers and 60 students who took part in theoretical sessions, movement practice, and intensive mentoring. The results showed significant improvements: mastery of gymnastics movements increased from 18% to 95%, understanding of local cultural values rose from 30% to 92%, and readiness to implement the gymnastics in learning grew from 15% to 88%. Furthermore, participants demonstrated high enthusiasm throughout the activity. This training proved to be an effective innovation for PE learning that is enjoyable, contextual, and supports the preservation of local culture. The program has the potential to be developed into a regular school activity and inter-school competition in Gorontalo.